Network and Parallel Computing: 13th IFIP WG 10.3 International Conference, NPC 2016, Xi'an, China, October 28-29, 2016, Proceedings - Gao, Guang R; Qian, Depei; Gao, Xinbo; Chapman, Barbara; Chen, Wenguang (Lecture Notes in Computer Science, 2016)
This book constitutes the proceedings of the 13th IFIP WG 10.3International Conference on Network and Parallel Computing, NPC 2016,held in Xi'an, China, in October 2016.The 17 full papers presented were carefully reviewed and selected from 99 submissions. They are organized in the following topical sections; memory: non-volatile, solid state drives, hybrid systems; resilience and reliability; scheduling and load-balancing; heterogeneous systems; data processing and big data; and algorithms and computational models.